2020
DOI: 10.1016/j.yebeh.2020.107241
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected brain imaging findings in patients with seizures

Abstract: New imaging technologies have advanced our ability to localize the epileptogenic zone in patients with epilepsy. As a result of the constant improvement of the image quality, magnetic resonance imaging (MRI) has become the most important ancillary tool in the management of patients with epilepsy. Magnetic resonance imaging for the evaluation of patients with epilepsy should be done using a special temporal lobe protocol and read by physicians experienced with the findings in patients with epilepsy. On the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This cognitive bias is present when the result of a study is influenced by how the study is presented or how the question is asked [93]. Many neuroimaging findings associated with medication resistant epilepsy are subtle and are appreciated better with specialized imaging protocols [8,20,94,95]. Even though 45% of our MRIs were obtained at 3T and 23% were obtained with epilepsy protocol, the radiologists were challenged to evaluate uniformly for subtle, clinically relevant findings in a non-ideal setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cognitive bias is present when the result of a study is influenced by how the study is presented or how the question is asked [93]. Many neuroimaging findings associated with medication resistant epilepsy are subtle and are appreciated better with specialized imaging protocols [8,20,94,95]. Even though 45% of our MRIs were obtained at 3T and 23% were obtained with epilepsy protocol, the radiologists were challenged to evaluate uniformly for subtle, clinically relevant findings in a non-ideal setting.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, clinicians may presume that neuroimaging of patients with FS would be normal, and abnormal neuroimaging should cast doubt on the diagnosis. However, multiple retrospective studies have demonstrated radiologically apparent abnormalities in 30% of magnetic resonance images (MRIs) from patients with FS without comorbid ES [7][8][9][10][11][12][13][14]. While the majority of these abnormalities were nonspecific, two previous studies found that 5-10% of them had definitive epilepsy-associated findings (EAF) including hippocampal sclerosis [7,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Combination PNES/epilepsy patients were more likely to have epileptogenic structural brain abnormalities (such as tumors, mesial temporal sclerosis, encephalomalacia, and developmental anomalies [23]. However, previous studies, including ours, lacked adequacy due to being ex post facto and not including healthy controls [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 65%
“…Only about a quarter of the 130 participants with PNES in this study had a brain MRI. In most cases, it is clinically reasonable and appropriate to do a magnetic resonance imaging scan of the brain of individuals with epilepsy [ 17 ]. Sixty percent of patients in recent studies of 224 people with PNES solely had brain MRI [ 18 ].…”
Section: Discussionmentioning
confidence: 99%